2018
DOI: 10.1021/acs.joc.8b02286
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Aminoisoquinolines via Rh(III)-Catalyzed C–H/N–H Bond Functionalization of N-Aryl Amidines with Cyclic 2-Diazo-1,3-diketones

Abstract: A simple C–H/N–H bond functionalization of N-aryl amidines with cyclic 2-diazo-1,3-diketones for the synthesis of 1-aminoisoquinolines has been accomplished by employing [Cp*RhCl2]2/CsOPiv as the catalyst system. This methodology proceeds by a cascade C–H activation/intramolecular cyclization under mild reaction conditions, features a broad substrate scope, and involves the formation of two new σ bonds (C–C and C–N) in a single operation for the construction of novel 1-aminoisoquinoline skeletons in good to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…In particular, 1‐aminoisoquinolines demonstrated great value in medical and pharmaceutical applications as antimalarial, antitumor and anticancer agents . Stimulated by their importance, in 2018 Shang and co‐workers developed a method for the selective synthesis of 1‐aminoquinolines 46 trough a Rh III ‐catalyzed C−H/N−H bond functionalization by using N‐aryl amidinies 44 and diazocompounds 45 . The classical [Cp*RhCl 2 ] 2 is used as catalyst in combination with CsOPiv as additive in order to obtain good yields of the desired heterocycles 46 through a cascade Rh III ‐catalyzed C−H bond functionalization followed by intramolecular nucleophilic attack from the amidine ( A ) and concomitant water elimination (Scheme ).…”
Section: Heterocycle Synthesis Through Cascade C−m→c−c→c−n Bond Formamentioning
confidence: 99%
“…In particular, 1‐aminoisoquinolines demonstrated great value in medical and pharmaceutical applications as antimalarial, antitumor and anticancer agents . Stimulated by their importance, in 2018 Shang and co‐workers developed a method for the selective synthesis of 1‐aminoquinolines 46 trough a Rh III ‐catalyzed C−H/N−H bond functionalization by using N‐aryl amidinies 44 and diazocompounds 45 . The classical [Cp*RhCl 2 ] 2 is used as catalyst in combination with CsOPiv as additive in order to obtain good yields of the desired heterocycles 46 through a cascade Rh III ‐catalyzed C−H bond functionalization followed by intramolecular nucleophilic attack from the amidine ( A ) and concomitant water elimination (Scheme ).…”
Section: Heterocycle Synthesis Through Cascade C−m→c−c→c−n Bond Formamentioning
confidence: 99%
“…reaction showed less efficient at both lower and higher temperatures (entries 12-13). The results were not improved by changing the catalyst loadings (entries [14][15]. And the reaction was totally supressed in the absence of catalyst (entry 16).…”
Section: Communications Ascwiley-vchdementioning
confidence: 99%
“…[12] Specifically, 1,3-dicarbonyl-2diazo compounds are typically used as C2 building blocks in the construction of cyclic compounds due to their propensity toward undergoing transition-metalcatalysed carbene insertion and subsequent condensation cyclization reactions. [13] Based on our long-standing research interests in this field, [14] we designed a free amino-directed Rh-catalysed carbene insertion reaction with 3-methyl-1-phenyl-1H-pyrazol-5-amine (1 a) and 2-diazo-5,5-dimethylcyclohexane-1,3-dione (2 a) as the substrates. However, an unexpected product, 3,7,7-trimethyl-1-phenyl-1,6,7,8-tetrahydro-5H-pyrazolo [3,4-b]quinolin-5-one (3 a), was generated when using Rh 2 (OAc) 2 as the catalyst and DMF as the solvent.…”
mentioning
confidence: 99%
“…One of the reasons for this is the absence of a general and reliable catalytic system for simultaneous activation of C−H bonds at different positions. It was observed that the o −C(sp 2 )−H bond of N ‐phenyl ring is specifically activated under identical conditions rather than C ‐ phenyl ring of amidine [14a,15,18] . Thus, it offers the possibility to exploit double C−H bond activation conducted by sequential difunctionalization of N ‐phenylbenzimidamide in one pot.…”
Section: Introductionmentioning
confidence: 99%